Desain Pengembangan Kurikulum Pendidikan Agama Islam Berbasis Teknologi di SMP Negeri 6 Kaur - Oktinan Toni, Jonsi (JPT : Jurnal Pendidikan Tematik, 2024)
The curriculum of Islamic education cannot be separated from its relationship with the basis and objectives of Islamic education. Some parts of the curriculum can be developed in accordance with the demands of the times and the human environment, but it is considered that the Islamic education curriculum must be substantially related to the objectives of Islamic education. Curriculum organization is regarded as capable of achieving these goals. Acting as a determinant of how a learning will take place, of course, the organization of this curriculum becomes one of the important factors. Curriculum design is a framework in preparing the curriculum organization and is the preparation of one of the curriculum components, namely the content of curriculum materials. This research uses library research by analyzing data, documents related to the discussion are analyzed systematically. The purpose of this study is to determine the form of PAI curriculum organization, PAI curriculum design principles, and the form of PAI curriculum design. The curriculum development process should be oriented towards the ability of students to recognize and image technological products that have long been used by the Indonesian people in accordance with the advancement of science and technology. Technology-integrated curriculum development will develop learners' critical thinking. Using technology as a learning tool provides effective learning strategies and classroom management for teachers in education units.